Chemical weathering in the upper and middle reaches of Yarlung Tsangpo River - Cheng, Yu; Wang, Rui; Liu, Zhaofei; Yao, Zhijun (Frontiers in Environmental Science, 2024)
This study focused on the chemical composition of the rivers in the middle and upper reaches of the Yarlung Tsangpo River system. Samples were collected in April 2015 to analyze spatiotemporal variation characteristics and determine weathering processes and CO2 consumption using principal component analysis (PCA) and a modified forward model. The TDS on the southern bank of the upper and middle reaches of the Yarlung Tsangpo basin was found to be higher than that on the northern bank because of the difference in stratigraphic structure. The results show that the chemical facies of the rivers all belonged to Ca-HCO3, and the rate of sulfuric acid-dominated chemical weathering was extremely high in the sub-watershed by TZ +⁎ /HCO3 -⁎ . Four major reservoirs (precipitation, silicates, carbonates, and evaporites) produce ions. The results of the chemical budget show that their contribution rates were 7.80% vs. 5.09% (PCA vs. modified forward model, the same below): 21.8% vs. 24.7%, 42.80% vs. 50.22%, and 10.30% vs. 21.59%, respectively. The ionic components from carbonate weathering in the study area were dominant, which is the main reason why the calculated results of the carbonate weathering rate (CWR) were higher than the silicate weathering rate (SWR).The CWR reached its maximum value during the monsoon period, whereas the SWR showed the opposite trend. Moreover, CO2 sequestration by chemical weathering of rivers might be the main carbon sink in Tibet, which contributes to the realization of carbon neutrality in Tibet.